Pengaruh Quality Of Website, Brand Resonance Dan Online Customer Review Terhadap Purchase Intention Pada Konsumen Agoda.Com Di Surabaya - Ira Ningrum Resmawa; Siti Masruroh (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2022)
Information technology is very helpful for consumers as a means of supporting longdistancecommunication at this time where consumers can easily use the internet to accessapplications that can help consumers to get what they want, such as those engaged inhospitality and tourism services such as Agoda. The focus of this research is to determinehow the influence of Quality of Website, Brand Resonance and Online Customer Reviewon Purchase Intention of Agoda.com consumers in Surabaya. The results show that thequality of the website has a significant influence on the Purchase Intention of Agoda.comconsumers. Brand Resonance has a significant influence on the purchase intention ofAgoda.com consumers. Meanwhile, online customer reviews have no significant effect onthe purchase intention of Agoda.com consumers.